Psikoedukasi “Bidan Cerdas” untuk Menurunkan Stigma terhadap Orang dengan HIV/AIDS (ODHA) - Adhesatya Ningsih Moodoeto; Esti Hayu Purnamaningsih (Gadjah Mada Journal of Professional Psychology (GamaJPP), 2017)
Lack of knowledge about HIV /AIDS makes people including health workers stigmatize people living with HIV (PLWHA). It has a negative impact on PLWHA because of the constraints of quality of service, lowering of health, the reluctance of VCT, and non-compliance of ARVs. The aim of this research to reduce the stigma of midwives against PLWHA through psychoeducation program of "Biden Cerdas". The subject of this research is the midwife. This research uses the experiment design of Non-Random Untreated Kontrol Group Design with Dependent Pretest and Posttest Samples. Stigma to PLWHA measurement uses stigma scale developed by Genberg, et., al (2009). The research hypothesis was tested with Mixed Design ANOVA. The results of the analysis in the experimental group showed p<0.05 in the Pre Test to Post Test, and p<0.05 on Post Test data to Follow Up. It concluded that psychoeducation program of "Bidan Cerdas" can reduce stigma against PLWHA.